Anthropomorphism for wildlife: the effects of anthropomorphic cues and phylogenetic closeness on perceived animal-human similarity, conservation intention, and donation behavior - Shiu, Pedro Pui Kar (Nanyang Technological University, 2024)
The use of anthropomorphic animal messengers (AAMs) is a popular practice in the field of conservation communication. Research has shown that the use of AAMs can promote conservation intention among audiences. However, there is little study on what variables enable an AAM to be effective. Drawing upon construal level theory, this study examines the effects of visual and language anthropomorphic cues on donation behavior, conservation intention, and perceived animal-human similarity. This study also examines whether perceived animal-human similarity and conservation intention mediate the effects of anthropomorphic cues on donation behavior. This study evaluates if phylogenetic closeness moderates the effect of anthropomorphic cues on perceived animal-human similarity. Hypothesis testing involved an online between-subjects experiment (N = 352) that manipulated the presence of anthropomorphic cues and phylogenetic closeness in a series of short conservation videos. Data analysis involved a series of simple linear regressions, analysis of covariance, and mediation analysis. The study that found that anthropomorphic cues had no effect on donation behavior, conservation intention, and perceived animal-human similarity. Anthropomorphic cues also had no indirect effects on donation behavior through perceived animal-human similarity and conservation intention. Finally, phylogenetic closeness had no moderating effect on anthropomorphic cue’s influence on perceived animal-human similarity.